Download presentation

Presentation is loading. Please wait.

Published byErin Byrd Modified over 3 years ago

1

2
Differential calculus is concerned with the rate at which things change. For example, the speed of a car is the rate at which the distance it travels changes with time. First we shall review the gradient of a straight line graph, which represents a rate of change.

3
Gradient of a straight line graph The gradient of the line between two points (x 1, y 1 ) and (x 2, y 2 ) is where m is a fixed number called a constant. A gradient can be thought of as the rate of change of y with respect to x.

4
Gradient of a curve A curve does not have a constant gradient. Its direction is continuously changing, so its gradient will continuously change too. The gradient of a curve at any point on the curve is defined as being the gradient of the tangent to the curve at this point. y = f(x)

5
, as we know only one point on the tangent and we require two points to calculate the gradient of a line. A tangent is a straight line, which touches, but does not cut, the curve. x y O A Tangent to the curve at A. We cannot calculate the gradient of a tangent directly

6
Using geometry to approximate to a gradient x O y A Tangent to the curve at A. B1B1 B2B2 B3B3 Look at this curve. Look at the chords AB 1, AB 2, AB 3,... For points B 1, B 2, B 3,... that are closer and closer to A the sequence of chords AB 1, AB 2, AB 3,... move closer to becoming the tangent at A. The gradients of the chords AB 1, AB 2, AB 3,... move closer to becoming the gradient of the tangent at A.

7
A numerical approach to rates of change Here is how the idea can be applied to a real example. Look at the section of the graph of y = x 2 for 2 > x > 3. We want to find the gradient of the curve at A(2, 4). A (2, 4) B 1 (3, 9) B 2 (2.5, 6.25) B 3 (2.1, 4.41) B 4 (2.001, ) The gradient of the chord AB 1 is Chord x changes from y changes from gradient AB 1 AB 2 AB 3 AB 4 AB 5 2 to 3 4 to 9 = 5 2 to to 6.25 = to to 4.41 = to to = to to Complete the table

8
As the points B 1, B 2, B 3,... get closer and closer to A the gradient is getting closer to 4. This suggests that the gradient of the curve y = x 2 at the point (2, 4) is 4. x y 2 4 y = x 2 It looks right to me.

9
Find the gradient of the chord joining the two points with x-coordinates 1 and on the graph of y = x 2. Make a guess about the gradient of the tangent at the point x = 1. Example (1) (1, ) (1.001, ) ) = The gradient of the chord is Id guess 2.

10
Find the gradient of the chord joining the two points with x-coordinates 8 and on the graph of y = x 2. Make a guess about the gradient of the tangent at the point x = 8. Example (2) (8, ) (8.0001, ) The gradient of the chord is = Id guess 16.

11
Lets make a table of the results so far: x-coordinategradient I think I can sees a pattern but can I prove it?

12
(2, 4) (2 + h, (2 + h) 2 ) I need to consider what happens when I increase x by a general increment. I will call it h. h I will call it x.

13
Let y = x 2 and let A be the point (2, 4) x y A(2, 4) y = x 2 O B(2 + h, (2 + h) 2 ) Let B be the point (2 + h, (2 + h) 2 ) Here we have increased x by a very small amount h. In the early days of calculus h was referred to as an infinitesimal. Draw the chord AB. Gradient of AB = 4 + h As h approaches zero, 4 + h approaches 4. So the gradient of the curve at the point (2, 4) is 4. Use a similar method to find the gradient of y = x 2 at the points (i) (3, 9) (ii) (4, 16) If h 0 we can cancel the hs.

14
We can now add to our table: x-coordinategradient It looks like the gradient is simply 2x. 6868

15
Lets check this result. y = x 2

16
Lets check this result. y = x 2 Gradient at (3, 9) = 6

17
Lets check this result. y = x 2 Gradient at (2, 4) = 4

18
Lets check this result. y = x 2 Gradient at (1, 1) = 2

19
Lets check this result. y = x 2 Gradient at (0, 0) = 0

20
Lets check this result. y = x 2 Gradient at (–1, 1) = –2

21
Lets check this result. y = x 2 Gradient at (–2, 4) = –4

22
Lets check this result. y = x 2 Gradient at (–3, 9) = –6

23

24
Another way of seeing what the gradient is at the point (2, 4) is to plot an accurate graph and zoom in. ZOOM IN y = x 2

25
When we zoom in the curve starts to look like a straight line which makes it easy to estimate the gradient

26
Using a similar approach to that in the previous slide show it is possible to find the gradient at any point (x, y) on the curve y = f(x). At this point it is useful to introduce some new notation due to Leibniz. The Greek letter (delta) is used as an abbreviation for the increase in. Thus the increase in x is written as x, and the increase in y is written as y. P (x 1, y 1 ) Q (x 2, y 2 ) x y O So when considering the gradient of a straight line, x is the same as x 2 – x 1 andy is the same as y 2 – y 1. x y Gottfried Leibniz gradient Note x is the same as h used on the previous slide show.

27
Gradient of the curve y = x 2 at the point P( x, y ) Suppose that the point Q(x + x, y + y) is very close to the point P on the curve. The small change from P in the value of x is x and the corresponding small change in the value of y is y. It is important to understand that x is read as delta x and is a single symbol. The gradient of the chord PQ is: x O y P(x, y) Q(x + x, y + y) y = x 2 x y y x y The coordinates of P can also be written as (x, x 2 ) and the coordinates of Q as [(x + x), (x + x) 2 ]. So the gradient of the chord PQ can be written as: = 2x + x

28
So = 2x + x As x gets smaller approaches a limit and we start to refer to it in theoretical terms. This limit is the gradient of the tangent at P which is the gradient of the curve at P. It is called the rate of change of y with respect to x at the point P. For the curve y = x 2, = 2x This is the result we obtained previously. This is denoted by or.

29
Gradient of the curve y = f( x ) at the point P( x, y ) x O y P(x, y) Q(x + δx, y + δy) y = f(x) x y y δx δy For any function y = f(x) the gradient of the chord PQ is: The coordinates of P can also be written as (x, f(x)) and the coordinates of Q as [(x + δx), f(x + δx)]. So the gradient of the chord PQ can be written as:

30
It is defined by In words we say: The symbol is called the derivative or the differential coefficient of y with respect to x. dee y by dee x is the limit of as δx tends to zero tends to is another way of saying approaches DEFINITION OF THE DERIVATIVE OF A FUNCTION DEFINITION OF THE DERIVATIVE OF A FUNCTION

31
Sometimes we write h instead of x and so the derivative of f(x) can be written as DEFINITION OF THE DERIVATIVE OF A FUNCTION DEFINITION OF THE DERIVATIVE OF A FUNCTION

32
If y = f(x) we can also use the notation: = f (x) In this case f is often called the derived function of f. This is also called f-prime. The procedure used to find from y is called differentiating y with respect to x.

33
Find for the function y = x 3. Example (1) In this case, f(x) = x 3. = 3x 2 f(x) x2x2 2x2x x3x3 3x23x2 Results so far

34
y = x 3

35
Gradient at (2, 8) = 12

36
Find for the function y = x 4. Example (2) In this case, f(x) = x 4. = 4x 3 Results so far f(x) x2x2 2x2x x3x3 3x23x2 x4x4 4x34x3

37
Find for the function y =. Example (3) In this case, f(x) =.

38
So we now have the following results: We also know that if y = x = x 1 then and if y = 1 = x 0 then These results suggest that if y = x n then It can be proven that this statement is true for all values of n. nxnxn –1 2x2x2 2x2x 3x3x3 3x23x2 4x4x4 4x34x3

39
Find for the function y = 1. Example (1) y = 1 can be thought of as y = x 0. Using = 0 But of course we knew this already. y = 1 1 y x O

40
Find for the function y = x. Example (2) y = x can be thought of as y = x 1. Using = 1 = x 0 But of course we knew this already. y = x y x O

41
Find for the function y = x 2. Example (3) Using = 2x

42
Find for the function y = x 3. Example (4) Using = 3x 2

43
Find for the function y = x 4. Example (5) Using = 4x 3

44
Find for the function y =. Example (6) Using = –x –2 y = can be written as y = x –1.

45
Find for the function y =. Example (7) Using = –2x –3 y = can be written as y = x –2.

46
Find for the function y =. Example (8) Using y = can be written as.

47
Find for the function y =. Example (9) Using y = can be written as.

48
Most of the functions we meet are not powers of the single variable x but consist of a number of terms such as y = 2x 2 + 3x + 5. The following rules can be proven: If you multiply a function by a constant, you multiply its derivative by the same constant. If f(x) = ag(x), then f (x) = ag (x). This is because multiplying a function by a constant a has the effect of stretching the function in the y direction by a scale factor a which increases the gradient by the factor a. If you add two functions, then the derivative of the sum is the sum of the derivatives. If f(x) = g(x) + h(x), then f (x) = g (x) + h (x). However if you multiply two functions, then the derivative of the product is NOT the product of the derivatives.

49
Find for the function y = 3x 2. Example (1) = 6x

50
Find for the function y = 8x 3. Example (2) = 24x 2

51
Find for the function y = x 4 + x 3. Example (3)

52
Find for the function y = x 2 + x + 1 Example (4) = 2x + 1

53
Find the gradient of the curve y = 2x 2 + 3x – 7 at the point (2, 7). Example (5) At the point (2, 7), So the gradient = 11

54
Find for the function Example (6)

55
Find the coordinates of the points on the graph of y = 2x 3 – 3x 2 – 36x + 10 at which the gradient is zero. Example (7) Let f(x) = 2x 3 – 3x 2 – 36x + 10 Then f (x) = 6x 2 – 6x – 36 The gradient is zero when f (x) = 0 That is when 6x 2 – 6x – 36 = 0 This simplifies to x 2 – x – 6 = 0 In factor form this is (x – 3)(x + 2) = 0 So x = –2 or x = 3 Substituting these values into y = 2x 3 – 3x 2 – 36x + 10 to find the y-coordinates gives y = 54 and y = –71 The coordinates of the required points are therefore (–2, 54) and (3, –71)

56
x y O A Tangent Normal The tangent at the point A(a, f(a)) has gradient f (a). We can use the formula for the equation of a straight line, y – y 1 = m(x – x 1 ) to obtain the equation of the tangent at (a, f(a)). The equation of the tangent to a curve at a point (a, f(a)) is y – f(a) = f(a)(x – a) The normal to the curve at the point A is defined as being the straight line through A which is perpendicular to the tangent at A. The gradient of the normal is as the product of the gradients of perpendicular lines is –1. The equation of the normal to a curve at a point (a, f(a)) is

57
12 Example (1) The curve C has equation y = 2x 3 + 3x The point A with coordinates (1, 7) lies on C. Find the equation of the tangent to C at A, giving your answer in the form y = mx + c, where m and c are constants. = 6x 2 + 6x At x = 1, the gradient of C = Equation of the tangent at A is y = 12x – 5 which simplifies to y – 7 = 12(x – 1)

58
Example (2) A B x y O C l The diagram shows the curve C with the equation y = x 3 + 3x 2 – 4x and the straight line l. The curve C crosses the x-axis at the origin, O, and at the points A and B. (a) Find the coordinates of A and B. The line l is the tangent to C at O. (b) Find an equation for l. (c) Find the coordinates of the point where l intersects C again. (a) y = x 3 + 3x 2 – 4x So A is (–4, 0) and B is (1, 0) (b) At O, So an equation for l is y = –4x (c) x 3 + 3x 2 – 4x = –4x = x(x + 4)(x – 1) x 3 + 3x 2 = 0 x 2 (x + 3) = 0 So l intersects C again when x = –3 and y = 12 So the coordinates of the point of intersection are (–3, 12) = x(x 2 + 3x – 4)

59
Example (3) For the curve C with equation y = x 4 – 9x 2 + 2, (a) find The point A, on the curve C, has x-coordinate 2. (b) Find an equation for the normal to C at A, giving your answer in the form ax + by + c = 0, where a, b and c are integers. (a) y = x 4 – 9x = 4x 3 – 18x (b) When x = 2, y = –18. So the coordinates of A are (2, –18). When x = 2, gradient of C = 4 8 – 18 2 = –4 So the gradient of the normal = Equation of the normal to C at A is which simplifies to x – 4y – 74 = 0

60
A curve C has equation y = 2x 2 – 6x + 5. Example (4) The point A, on the curve C, has x-coordinate 1. (a) Find an equation for the normal to C at A, giving your answer in the form ax + by + c = 0, where a, b and c are integers. The normal at A cuts C again at the point B. (b) Find the coordinates of the point B. When x = 1, y = 2 – = 1 Gradient of the tangent to the curve at A = 4 – 6 = –2 which simplifies to x – 2y + 1 = 0 (a) = 4x – 6 4x 2 – 12x + 10 = x + 1 4x 2 – 13x + 9 = 0 (x – 1)(4x – 9) = 0 Gradient of the normal to the curve at A = Equation of the normal to the curve at A is (b) 2x 2 – 6x + 5 = So x-coordinate of B = y-coordinate of B =

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google